Expression of tardigrade disordered proteins impacts the tolerance to biofuels in a model cyanobacterium Synechocystis sp. PCC 6803 - Zhang, Heao; Liu, Qingyang; Liang, Qing; Wang, Boxiang; Chen, Zixi; Wang, Jiangxin (Frontiers in Microbiology, 2023)
Tardigrades, known colloquially as water bears or moss piglets, are diminutive animals capable of surviving many extreme environments, even been exposed to space in low Earth orbit. Recently termed tardigrade disordered proteins (TDPs) include three families as cytoplasmic-(CAHS), secreted-(SAHS), and mitochondrial-abundant heat soluble (MAHS) proteins. How these tiny animals survive these stresses has remained relatively mysterious. Cyanobacteria cast attention as a “microbial factory” to produce biofuels and high-value-added chemicals due to their ability to photosynthesis and CO2 sequestration. We explored a lot about biofuel stress and related mechanisms in Synechocystis sp. PCC 6803. The previous studies show that CAHS protein heterogenous expression in bacteria, yeast, and human cells increases desiccation tolerance in these hosts. In this study, the expression of three CAHS proteins in cyanobacterium was found to affect the tolerance to biofuels, while the tolerance to Cd2+ ¬and Zn2+ were slightly affected in several mutants. A quantitative transcriptomics approach was applied to decipher response mechanisms at the transcriptional level further.